Patterns of Genetic Diversity and Gene Flow Associated With an Aridity Gradient in Populations of Common Mole-rats, Cryptomys hottentotus hottentotus - Merchant, HN; Ivanova, A; Hart, DW; García, C; Bennett, NC; Portugal, SJ; Faulkes, CG (Oxford University Press, 2024)
Genetic adaptation is the change of a population toward a phenotype that best fits the present ecological conditions of the environment it inhabits. As environmental conditions change, allele frequencies shift, resulting in different populations of the same species possessing genetic variation and divergent phenotypes. Cooperatively breeding common mole-rats (Cryptomys hottentotus hottentotus) inhabit environments along an aridity gradient in South Africa, which provides an opportunity for local genetic adaptations to occur. Using one mitochondrial gene (cytochrome b) and 3,540 SNP loci across the whole genome, we determined the phylogenetic relationship, population structure and genetic diversity of five populations of C. h. hottentotus located along an aridity gradient. Mitochondrial data identified population-specific clades that were less distinct in the two mesic populations, potentially indicating historical or recent gene flow, or the retention of ancestral haplotypes. Arid and semi-arid populations formed a distinct cluster from the non-arid populations. Genetic diversity and gene flow were higher in arid-dwelling individuals, suggesting greater connectivity and interactions between colonies in arid regions in comparison to mesic ones. Using an Aridity Index, we determined that isolation by environment, rather than isolation by geographical distance, best explains the genetic distance between the populations. Further analyses using target loci may determine if there are differing underlying genetic adaptations among populations of C. h. hottentotus. These analyses could help unravel population differences in response to environmental factors within a subspecies of bathyergid mole-rat and determine the adaptive capacity of this small nonmigratory subterranean rodent species in response to aridification in the face of climate change.